Spectroscopic Analysis of Heterogeneous Biocatalysts for Biodiesel Production from Expired Sunflower Cooking Oil - Enoch Wembabazi; Patrick Joram Mugisha; Asumani Ratibu; Deborah Wendiro; Joseph Kyambadde; Peter California Vuzi (Journal of Spectroscopy)
The study characterized heterogeneous biocatalyst synthesized from sucrose, saw dust, and chicken egg shells using Fourier Transform Infrared (FTIR) spectroscopy coupled with Attenuated Total Reflectance (ATR) technique. Acidic sulphonate (–SO3H) groups were more visible in the spectrum generated for carbonized and sulphonated sucrose than in carbonized and sulphonated saw dust. This was highlighted further by the significantly higher conversion percentage achieved for sulphonated sucrose (62.5%) than sulphonated saw dust (46.6%) during esterification of expired sunflower oil (p=0.05). The spectra for calcinated egg shells also showed that the most active form of calcium oxide was produced at calcination temperature of 1000°C. This was confirmed in the single-step transesterification reaction in which calcium oxide generated at 1000°C yielded the highest biodiesel (87.8%) from expired sunflower oil. The study further demonstrated the versatility of the FTIR technique in qualitative analysis of biodiesel and regular diesel by confirming the presence of specific characteristic peaks of diagnostic importance. These findings therefore highlight the potential of FTIR-ATR as an inexpensive, fast, and accurate diagnostic means for easy identification and characterization of different materials and products.